Comparative Roles of Mediators in Non-Litigation Dispute Resolution: Indonesia and Thailand - Abdulloh Tsani Harahap; Zainuddin Zainuddin (JURNAL USM LAW REVIEW, 2026)
This study aims to comparatively analyze the role of mediators in non-litigation dispute resolution in Indonesia and Thailand and to examine how differences in legal and sociological orientations influence mediation effectiveness. Existing mediation studies predominantly focus on procedural or institutional aspects, leaving a limited understanding of how mediator positioning as legal and social actors affects dispute resolution outcomes. This research employs a normative legal method using statutory and comparative law approaches, supported by the analysis of legislation, legal doctrines, and scholarly literature. The findings reveal that Indonesia adopts a formal and legalistic mediation model in which mediators function as certified facilitators to ensure legal certainty and enforceability, but with relatively limited social acceptance. In contrast, Thailand applies a community-based mediation model that positions mediators as socially legitimate actors capable of fostering trust and voluntary compliance, although with weaker formal legal guarantees. This study contributes to mediation scholarship by conceptualizing mediators as hybrid legal–social institutions whose effectiveness depends on balancing juridical authority and social legitimacy. The findings imply that developing an integrative mediation framework combining legal certainty with sociological legitimacy is essential to strengthen the effectiveness, accessibility, and sustainability of non-litigation dispute resolution systems.
Keywords: Alternative Dispute Resolution; Comparative Law; Dispute Resolution; Mediation